Determinants of MSME Sustainability in Emerging Asia: A Systematic Review - Fajar Ayu Pinagara; Ratih Dyah Kusumastuti; Ruslan Prijadi; Permata Wulandari (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2025)
This study reviews the state of knowledge on MSME sustainability with a focus on empirical research in emerging Asian countries. By employing a combination of bibliometric analysis and systematic literature review (SLR) techniques, the study draws upon a comprehensive pool of 950 articles sourced from the SCOPUS and Web of Science databases to evaluate trends, gaps, and scholarly contributions within this domain. Results show a clear rise in MSME-sustainability research over the past decade, with Indonesia and India leading scholarly output. Yet several drivers and themes remain underexplored, revealing both theoretical and practical gaps. As the first systematic effort to synthesize research on MSME sustainability within the context of emerging Asian economies, the study offers original insights and a structured agenda for future research. Given MSMEs’ central role in development and their relevance to the SDGs, the findings underscore the need for targeted inquiry and stronger policy support to advance effective sustainability strategies in the region.